IMPLEMENTASI KEBIJAKAN PELAYANAN PENUMPANG ANGKUTAN PELABUHAN PENYEBERANGAN SUNGAI SELARI-AIR PUTIH KABUPATEN BENGKALIS TAHUN 2023 - Zikri, Muhammad Al; ', isril (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Rapid developments in maritime transportation have increased the number of people traveling and transporting goods between regions. To balance this increase, transportation providers need to provide a service with optimal value intended for passengers and goods. A number of regulations have been implemented, including